Generational Marketing and Advertising: Influencing Purchase Intention in Generation X, Y, and Z in Viet Nam - Minh Triet, Phan Cong (Digital Repository of Theses - SSBM Geneva, 2025)
This study aims to examine the differences between Gen X, Gen Y and Gen Z consumers in Vietnam in terms of their interaction with advertising and their purchase intentions. The study shows that rapid global digital transformation also affects Vietnam and therefore, also reshapes consumer interaction behavior towards the advertising content delivered. This study finds that businesses need to adjust their advertising strategies according to different generational groups in order to create meaningful and effective advertising content for them. Age differences create different ways of interacting with advertising media such as through media, social media marketing, and short-form videos. Basically, the survey participants all agree on the influence of digital advertising in today's era, but there are still differences in the level of interaction and trust between generational groups with each advertising content they receive. Using a mixed methods approach, the study provides a detailed breakdown of the preferences of each buyer group. Gen X prefers traditional media advertising, valuing content that is informative, trustworthy, and shared. Gen Y is more engaged with social media advertising, valuing authenticity and ethical issues. Generation Z is most engaged with digital advertising, inspired by engaging short-form video ads, and influenced by social media influences. Overall, their purchasing decisions are strongly influenced by social media trends. The study also provides valuable insights for businesses to build advertising methods optimized for each generation’s preferences.